The development of english language reading fluency in high school students. - Albiño Guano, Daniela Lucia; Banchon Jaen, Amy Betsaida (Machala, UTMACH, 2023)
The present project is a quantitative methodological research paradigm, with a pre-experimental design that seeks to address the problem that exists in the high school students of the "Carmen Mora de Encalada" school concerning fluency in reading in the teaching-learning of the English language. On this basis, a system of classes is developed based on the use of didactic techniques that contribute to the development of reading fluency in the English language in high school students of the "Carmen Mora de Encalada" school. It assumes theoretical research methods such as historical-logical and analytical-synthetic, in addition to empirical methods such as experimentation, standardized tests, and statistical tests to provide a solution to the research question posed. How do we develop reading fluency in the English language in high school students at the Carmen Mora de Encalada School? The possible causes are: receptive skills are underestimated in the English language teaching and learning process, lack of reading comprehension, irrelevance to the reading action, and low student motivation and participation.
El presente proyecto es una investigación sujeta a un paradigma metodológico cuantitativo, con un diseño pre-experimental que busca abordar la problemática que existe en los estudiantes de bachillerato del colegio “Carmen Mora de Encalada” con respecto a la fluidez en la lectura de la enseñanza-aprendizaje del idioma inglés. Con esta base se elabora un sistema de clases basados en el uso de técnicas didácticas que aporten al desarrollo de la fluidez de la lectura del idioma inglés en estudiantes de bachillerato del colegio “Carmen Mora de Encalada”. Asume métodos teóricos de investigación como: el histórico-lógico y el analítico-sintético, además de métodos empíricos tales como: experimentación, pruebas estandarizadas y pruebas estadísticas a fin de dar solución a la pregunta de investigación planteada. ¿Cómo desarrollar la fluidez en la lectura del idioma inglés en estudiantes de bachillerato del Colegio Carmen Mora de Encalada?, cuyas posibles causales son: las habilidades receptivas son subestimadas dentro de la enseñanza-aprendizaje del inglés, falta de comprensión lectora, irrelevancia hacia la acción lectora, poca motivación y participación de parte del estudiante.
Keywords: TÉCNICA DIDÁCTICA; HABILIDAD DE LECTURA; FLUIDEZ LECTORA; DESARROLLO DE LA FLUIDEZ LECTORA; PROCESO DE ENSEÑANZA-APRENDIZAJE